PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK PADA MATERI TEOREMA PHYTAGORAS - Trisna Rukhmana; Al Ikhlas (LPPM Universitas Muhammadiyah Muara Bungo, 2019)
The study was a research and development aimed at developing learning package based on scientific approach, On Material Teorema Phytagoras which was valid, practical, and effective for Junior High School’s students. The development procedure used in the study was based on Thiagarajan’s model or 4-D model consisted of four phases, namely defining, designing, developing, and dissemination. The development learning package based on scientific approach had been validated by the experts and practitioners and had been revised; thus, it obtained feasible result to be used. The results revealed that the learning package based on scientific approach was valid, practical, and effective. The learning package that were RPP, student’s book, and student’s worksheet was valid due to the extremely valid category, practical because it was in completely conducted and effective as well because it had met the criteria of effective.